"To feel close when miles apart": qualitative analysis of motivations to sext in a relationship. Issue 2 (2nd April 2020) - Currin, Joseph M.; Pascarella, Lauren A.; Hubach, Randolph D.
Abstract: The current study sought to explore the motivations adults have for engaging in sexting behaviours with their relationship partners. Previous research mainly focuses on emerging adult and adolescent populations. With estimates of adults engaging in sexting approaching 50%, the current study used a qualitative approach to analyse responses from participants about their motivations to sext their relationship partners. With 157 (79 male) valid responses, the majority (86) of respondents identified sex related reasons for engaging in sexting. However, a sizeable minority (50) identified a non-sex related reason of physical distance from their partner(s) as a motivation to sext. This unique finding highlights the benefit that individuals who are physically separated from their partners gain by engaging in sexting. Participants in the current study shared aspects of engaging in sexting that were similar to other motivations found in previous research on sexting, but they framed these within the construct of being physically separated from their relationship partner(s). The results imply that distance may be an underlying motivation for some adults who engage in sexting behaviours with their partner(s).